Influence of time, toothpaste and saliva in the retention of Streptococcus mutans and Streptococcus sanguinis on different toothbrushes - Julia Caroline SCHMIDT; Miriam BUX; Elisabeth FILIPUZZI-JENNY; Eva Maria KULIK; Tuomas WALTIMO; Roland WEIGER; Clemens WALTER (University of São Paulo, 2014)
Objectives: The intraoral transmission of cariogenic and periodontopathogenic species seems to be facilitated by contaminated toothbrushes and other oral hygiene devices. The aim of this investigation was to analyze the in vitro retention and survival rate of Streptococcus mutans and Streptococcus sanguinis on different toothbrushes. The impacts of human saliva and antimicrobial toothpaste on these parameters were further evaluated. Material and Methods: Part I: Four toothbrushes (Colgate 360°, Curaprox CS5460 ultra soft, elmex InterX, Trisa Flexible Head3) were contaminated by S. mutans DSM 20523 or S. sanguinis DSM 20068 suspensions for three minutes. Bacteria were removed from the toothbrushes after either three minutes (T0) or 24 hours (T24) of dry storage and grown on Columbia blood agar plates for the quantification of colony-forming units (CFUs). Part II: The effects of saliva from a caries-active or a caries-inactive person and of toothpaste containing 0.12% chlorhexidine digluconate were also tested. Results: Part I: After three minutes of dry storage, approximately one percent of the bacteria were still detectable on the toothbrushes. After 24 hours, S. sanguinis exhibited a more pronounced decrease in viable cell numbers compared with S. mutans but the differences were not significant (Kruskal-Wallis test, p>0.05). Part II: The addition of human saliva from a caries-active or caries-inactive person slightly increased the retention of both streptococcal species at T0. The use of toothpaste had no influence on the amount of viable streptococci at T0, but it reduced the microbial load after 24 hours of storage. There were only slight nonsignificant differences (p>0.05) between the four toothbrushes. Conclusions: In vitro bacterial retention and survival of S. sanguinis and S. mutans on different toothbrushes occurred. Within the limitations of this study, the use of human saliva or an antimicrobial toothpaste did not lead to significant differences in the microbial load on toothbrushes.